A Biography That Humanizes its Subject: An Analysis of The Biography of Historian Onghokham - Nugraha, Iskandar (Prodi Ilmu Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, 2024)
A Biography That Humanizes its Subject: An Analysis of The Biography of Historian Onghokham